Perceptual video encryption using orthogonal matrix. Issue 3 (2nd October 2019) - Alhassan, Salamudeen; Iddrisu, Mohammed Muniru; Daabo, Mohammed Ibrahim
ABSTRACT: In this paper, the properties of rotation matrices are employed to construct special orthogonal matrices that are used to encrypt and decrypt video with varying perceptibility. Square orthogonal matrices of varying sides are formulated as cipher key matrices. The encryption algorithm uses these matrices to encrypt plain video into cipher video and transmit while the decryption algorithm uses the transpose of the cipher key matrices to recover the original video at the other end of the communication channel. Degradation in visual quality is controlled by varying cipher key dimension and the number of repetitions. Barring any noise in the communication channel, the proposed method retrieves the original video free of any error. Analysis of results show that the proposed method is key sensitive and resistant to chosen/known plain-text attacks.